Pengaruh Ease of Use, Security, Trust, dan Perception of Benefits terhadap Interest in Using Mobile Banking dengan Lifestyle Sebagai Variabel Moderating - Oktaviani, Mega; Engriani, Yunita (SAFE-Network, 2025)
This study aims to examine the effect of Ease of Use, Scurity, Trust, and Perception of Benefits on Interest In Using Mobile Banking with Lifestyle as a moderating variable on Padang City Students. This research is a quantitative study with a sample method, namely purposive sampling. The sample in this study were 121 respondents who were Padang State University students. The results of this study indicate that Ease of Use has no significant effect on interest in using Bank Nagari mobile banking in Air Tawar Padang, which means that this hypothesis is rejected because the p-value is 0.097> 0.05. The effect of Security, Trust, and Perception of Benefits has a significant positive effect on interest in using Bank Nagari mobile banking in Air Tawar Padang, which states that the p-value of each is